2009
DOI: 10.1063/1.3058899
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical description of charge migration with a single Slater-determinant and beyond

Abstract: Triggered by the interest to study charge migration in large molecular systems, a simple methodology has recently been proposed based on straightforward density functional theory calculations. This approach describes the time evolution of the initially created hole density in terms of the time evolution of the ionized highest occupied molecular orbital (HOMO). Here we demonstrate that this time-dependent analog of Koopmans' theorem is not valid, and instead of the time evolution of the HOMO, the time evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Whenever the excess charge is localized on a few atoms in a fragment, the approximation of preserved frontier orbitals may become problematic; then, a third-order expansion may account, for example, for the spatial expansion of the electron density in small anions with respect to the neutral molecules, as discussed for SCC-DFTB recently [48]. Also, it was shown that, after removing an electron from the HOMO, this orbital remains static and the charge migration is driven by lower lying orbitals [49]. We have tested this approximation for the nucleobase guanine, which is the dominant hole-carrying fragment in DNA.…”
Section: The Koopmans Theorem and The Zeroth-order Termmentioning
confidence: 99%
“…Whenever the excess charge is localized on a few atoms in a fragment, the approximation of preserved frontier orbitals may become problematic; then, a third-order expansion may account, for example, for the spatial expansion of the electron density in small anions with respect to the neutral molecules, as discussed for SCC-DFTB recently [48]. Also, it was shown that, after removing an electron from the HOMO, this orbital remains static and the charge migration is driven by lower lying orbitals [49]. We have tested this approximation for the nucleobase guanine, which is the dominant hole-carrying fragment in DNA.…”
Section: The Koopmans Theorem and The Zeroth-order Termmentioning
confidence: 99%
“…10 We note that using cDFT to create the initial state largely removes this problem, and makes charge migration dynamics possible.…”
Section: Discussionmentioning
confidence: 99%
“…After removing an electron due to sudden ionization of molecules by extreme ultraviolet (XUV) light, a hole is created which could be oscillating along different molecule sites. A purely electronic motion that takes place in its intrinsic time scale, few “fs” to “as,” is called charge (hole) migration, whereas the subsequent time evolution of molecule, from femto to pico seconds, including nuclear motion is designated as charge transfer [2, 3, 10, 11, 13–27]. Indeed, Charge migration analysis could be particularly important in governing early electronic dynamics, subsequent charge transfer [17] and photo‐induced chemical reactions.…”
Section: Introductionmentioning
confidence: 99%